Nutritional Challenges in Hemodialysis: Managing Protein Energy Wasting While Controlling Phosphorus - Jiaxiu Deng; Weixiang Luo; Xiumei Hu; Chao Yang (Clinical Case Reports)
ABSTRACT We present a case of a 72‐year‐old male on maintenance Hemodialysis, with protein energy wasting and mild phosphoremia managed through targeted nutritional intervention that focused on high‐biological value protein intake while maintaining phosphorus control. A multimodality approach including dietary modification and supplementation led to improvement in overall nutritional status.